Chrome dreams [compact disc] - Young, Neil, 1945- (Reprise, 2023)
One of Neil Young's legendary 'lost' albums that, for various reasons, he decided not to release at the time. Chrome Dreams features 12 songs recorded between 1974 and 1977. If the album was released in 1977 as originally planned, it would certainly be considered as one of the masterpieces in Neil's long career.